Is Moxifloxacin a Treatment Option for Pancreatic Infections? A Pharmacometric Analysis of Serum and Pancreatic Juice. (20th May 2019) - Wicha, Sebastian G.; Mundkowski, Ralf G.; Klock, Andrea; Hopt, Ulrich T.; Drewelow, Bernd; Kloft, Charlotte; Wellner, Ulrich F.; Keck, Tobias; Wittel, Uwe A.
Abstract: Postoperative local infection is a major complication after pancreatic surgery. The aim of this prospective clinical trial was to assess the potential of moxifloxacin (MXF) to treat pancreatic infections from a pharmacokinetic (PK)/pharmacodynamic (PD) perspective. The PK of MXF in serum and pancreatic juice, via an inserted tube in the pancreatic duct, was determined in 19 patients up to day 7 after pancreatoduodenectomy. PK data in both specimens was analyzed with NONMEM 7.3. Intraoperative swipes were performed for microbiological examination. PK/PD target attainment was assessed in both matrices using unbound area under the plasma concentration–time curve/minimum inhibitory concentration (MIC) targets of ≥30 and ≥100, for gram‐positive and gram‐negative pathogens, respectively. A 2‐compartment population PK model in which the measurements in pancreatic juice were assigned to a scaled peripheral compartment best described the PK in both specimens simultaneously. Median (10th–90th percentile) area under the plasma concentration–time curve values after the third dose were 28.9 mg · h/L (18.6–42.0) in serum and 55.8 mg · h/L (23.7–81.4) in pancreatic juice. Target attainment rate for the intraoperatively isolated bacterial strains was ≥0.88 after the third MXF dose. For gram‐negatives, high probability of target attainment ≥0.84 was observed in serum for MIC ≤ 0.125 mg/L and in pancreatic juice for MIC ≤ 0.25 mg/L. For gram‐positives, the probability of target attainment was 0.84–1 in serum for MIC ≤ 0.5 mg/L and in pancreatic juice for MIC ≤ 1 mg/L. In conclusion, penetration of MXF into pancreatic juice was substantial. The PK/PD analysis indicated that treatment of pancreatic infections by isolates with MIC ≤ 0.25 mg/L (gram‐negative) and ≤1 mg/L (gram‐positive) should be evaluated in further studies.